A LINE2 repetitive DNA sequence from the cichlid fish, Oreochromis niloticus: sequence analysis and chromosomal distribution - Oliveira, C.; Chew, JSK; Porto-Foresti, F.; Dobson, M. J.; Wright, J. M. (Springer, 1999)
We report the cloning and characterization of a long interspersed nucleotide element (LINE) fi-om a cichlid fish, Oreochromis niloticus, and show the distribution of this element, called CiLINE2 for cichlid LINE2, in the chromosomes of this species. The identification of an open reading frame in CiLINE2 with amino acid sequence similarity to reverse transcriptases encoded by LINE-like elements in Caenorhabditis elegans, Platemys spixii, Schistosoma mansoni, Gallus gallus (CRI), Drosophila melanogaster (I factor), and Homo sapiens (LINE2), as well as the structure of the element, suggest it is a member of this family of non-long terminal repeat-containing retrotransposons. Search of a DNA sequence database identified sequences similar to CiLINE2 in four other fish species (Haplotaxodon microlepis, Oreochromis mossambicus, Pseudotropheus zebra, and Fugu rubripes). Southern blot hybridization experiments revealed the presence of sequences similar to CiLINE2 in all Tilapiini species analyzed from the genera Oreochromis, Tilapia, and Sarotherodon, and gave an estimated copy number of about 5500 for the haploid genome of O. niloticus. Fluorescent in situ hybridization showed that CiLINE2 sequences were organized in small clusters dispersed over all chromosomes of O. niloticus, with a higher concentration near chromosome ends. Furthermore the long arm of chromosome 1 was strikingly enriched with this sequence. The distribution of LINE2-related elements might underlie the difference in chromosome banding patterns observed between cold-blooded vertebrates and mammals.